On creativity limits in contemporary society - Matsevich-Dukhan, Iryna Ja. (Journal of the Belarusian State University. Sociology, 2020)
The article exposes ontological, gnoseological, ethical and axiological aspects of the inquiry into creativity in social theory. Different approaches to the restriction of creativity in contemporary society are revealed. Its overexpansion and attempts to replace the social with the creative are discussed. Sociological and socio-philosophical approaches to the conditional restriction of the creativity value field and to the rehabilitation of the social are analysed.